Stories from My Childhood - Volume 2 - Ivanov-Vano, Ivan Petrovic; Babicenko, Dmitrij Naumovic; Lowe, Rob; Zuniga, Daphne; Murray, Bill (image Entertainment, 1999)
The featurettes in the Stories from My Childhood series were created at Soyuzmultfilm, the largest and most prominent studio in the old Soviet Union. California-based Films by Jove spent more than $1.5 million restoring the prints, adding new music and redubbing the films with major American actors. Based on fairy tales (some of them unfamiliar to American audiences), these mini-features are often charming examples of straightforward storytelling and colorful designs. "Ivan and His Magic Pony" (1947), usually called "The Little Hunch-Backed Horse", recounts the adventures of a young peasant boy who must capture a firebird, kidnap the lovely Seamaiden, and retrieve a ring from the bottom of the ocean. Its vision of swan-necked enchanted horses and flamboyant Byzantine palaces will delight children. Director Ivan Ivanov-Vano preserves the three-part structure of traditional fairy tales: Ivan is the youngest of three brothers, he must overcome three obstacles, etc. "Pinocchio and the Golden Key" (1959), or "The Adventures of Buratino", is based on Alexi Tolstoy's retelling of Carlo Collodi's famous tale of a living puppet. This more somber account of the little wooden boy is closer to the spirit of the original story, but pales in comparison to the opulently beautiful Disney feature. (Charles Solomon) [www.amazon.com]